Skin Biopsy: A New Tool to Diagnose Sarcoglycanopathy. (August 2014) - Chakrabarty, Biswaroop; Sharma, M.C.; Gulati, Sheffali; Kabra, Madhulika; Pandey, R.M.; Sarkar, Chitra
Muscular dystrophies are progressive, genetic disorders of muscle degeneration. The current gold standard for diagnosis is muscle biopsy or genetic studies. Muscle biopsy is an invasive procedure and genetic testing facilities are available only in a few centers. Thus, a diagnostic test that is easily available, simpler, and less invasive is desirable. Over the past 2 decades, skin biopsy has been evolving as a suitable option. Two cases of sarcoglycanopathy are described here, which have been correctly diagnosed by skin biopsy. Muscle biopsy has been used as the gold-standard diagnostic method. Skin biopsy can substitute for muscle biopsy as the preliminary diagnostic tool directing appropriate molecular testing. However, these results require validation in studies with an adequate sample size. This holds promise for the future when repeated biopsies will be required for evaluating protein rescue in trials of novel treatment options in these disorders.